Effects of pressure on arterial failure - Khamdaengyodtai P. (2014)
A three-dimensional multilayer model of mechanical response for analyzing the effect of pressure on arterial failure is presented in this work. The multilayer arterial wall is considered to be composed of five different layers. The three-dimensional effects are incorporated within the five-concentric axisymmetric layers while incorporating the nonlinear elastic characteristics under combined extension and inflation. Constitutive equations for fiber-reinforced material are employed for three of the major layers, i.e., intima, media and adventitia and an isotropic material model is employed for the other two layers, i.e., endothelium and internal elastic lamina. Our own developed three-dimensional five-layer model has been utilized to model propagated rupture area of the arterial wall. Required parameters for each layer are obtained by using a nonlinear least square method fitted to in vivo non-invasive experimental data of human artery and the effects of pressure on arterial failure are examined. The solutions from our computational model are compared with previous studies and good agreements are observed. Local stresses and strain distributions across the deformed arterial wall are illustrated and consequently the rupture area is predicted by varying luminal pressure in the physiological range and beyond. The effects of pressure on the arterial failure have been interpreted based on this comprehensive three-dimensional five-layer arterial wall model. This is the first study which employs two constitutive equations and incorporates a five-layer arterial wall model in three-dimensions based on in vivo non-invasive experimental data for a human artery. © 2012 Elsevier Ltd.